"What Has Become of Jimmy Thornton?": The Rhetoric(s) of Letter-Writing at The New York State Asylum for Idiots, 1855-1866 - Zosha Stuckey (Disability Studies Quarterly, 2011)
This article looks to the genre of letter-writing and to epistolary rhetoric in order to recover perspectives seemingly lost amongst the medicalized discourse of asylum histories. These hard-to-find letters written in the nineteenth century by pupils, family members, and teachers open us up to new perspectives not available in other archival documents. I give a brief introduction to the history and theory of epistolary rhetoric, delimit a disability epistolary, and then consider a group of letters in terms of the rhetorical action they perform. I conclude by emphasizing the significance of this cross-disciplinary work for both rhetoric and disability studies.
Keywords: Asylum; letters; rhetoric; Syracuse; history